Pengaruh Literasi Digital Berbasis Youtube Untuk Meningkatkan Kemampuan Pemecahan Masalah Fisika Siswa Kelas XI SMA Negeri 3 Sibolga - Anggun Fius Nadia Hasibuan; eni sumanti nasution; Evi Tamala (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2025)
In the process of learning physics, it usually requires a lot of practice so that media needs to be displayed to make it easier for students to understand. Education that develops all students' potential harmoniously and comprehensively, emphasizing problem-solving skills not only supports students' academic learning, but also prepares them to face the dynamics of the digital era. The purpose of this study was to determine how the influence of YouTube-based digital literacy on problem-solving abilities in physics learning in class XI students of SMA Negeri 3 Sibolga. In this study, the researcher used a quantitative experimental research method by selecting a sample of class XI MIA 1 as the control class and class XI MIA2 as the experimental class. From the results of the pretest and posttest in the control and experimental classes, the level of physics problem-solving abilities of the two classes was still very low, which can be seen from the average value and KKM of each class. However, after the learning process, the level of students' ability to solve physics problems increased for each class, but the most significant increase was especially in the experimental class that implemented YouTube-based digital literacy, which was 22.99%. The results of the statistical test showed that tcount 4.55> ttable 1.68, for a significance level of 95% and α = 0.05 so that Ha is accepted and H0 is rejected. This shows that the use of YouTube-based digital literacy media in learning fluid theory material can improve students' abilities in solving physics problems. The increase in students who have KKM in the control class is 38.89% and in the experimental class is 42.85. It can be concluded that the application of YouTube-based digital literacy to the physics problem-solving abilities of class XI students of SMA Negeri 3 Sibolga on Fluid subject matter is much more influential than conventional learning.. Keywords: Digital Literacy, Problem Solving, Physics.